Effect of Marketing Mix, Service Quality, and Consumer Satisfaction on the Decision to Purchase Mio M3 CW Motorcycle at PT. Hasjrat Abadi Unaaha - Melati Melati; Irham Natsir Kelana; Leni Saleh (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze how much effect of marketing mix, service quality, and consumer satisfaction on the decision to purchase Mio M3 CW Motorcycle at PT. Hasjrat Abadi Unaaha. The population in this study amounted to 80 respondents at PT. Hasjrat Abadi Unaaha, with sampling technique using saturated sampling technique. The analytical method used is multiple linear regression analysis. The results of this study indicate that simultaneously marketing mix, service quality, and customer satisfaction have a significant effect on the decision to purchase. Marketing mix has a negative and significant effect on the decision to purchase. Service quality has a positive and significant effect on the decision to purchase. Consumer satisfaction has a positive and significant effect on the decision to purchase.